Eksplorasi Sifat Analgesik Minyak Sereh Wangi: Bukti In Vivo pada Model Hewan Laboratorium - Dhini Andriani; Haryanto Haryanto (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Pain is a physiological response to tissue damage that can reduce quality of life if not treated properly. This study aims to evaluate the analgesic activity of Plant extract in mice (Mus musculus) as a laboratory animal model. Analgesic tests were carried out using the writhing test method to assess the peripheral analgesic effect and the hot plate test to assess the central analgesic effect. Mice were divided into several treatment groups that received Plant extract at different doses, as well as positive and negative controls. The results showed that administration of Plant extract significantly reduced the number of abdominal contractions in the writhing test and increased the latency time in the hot plate test compared to the negative control group (p < 0.05). The highest analgesic effect was found at the highest dose, and the results approached the effectiveness of the positive control.